Pengaruh Rasio Perbandingan Pome Dan Suspensi Mikroalga Pada Sistem Semikontinu Terhadap Laju Pertumbuhan Konsorsium Mikroalga - Wenny Andini; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Palm Oil Mill Effluent (POME) contains organic matter content and high pollutant load that contributes to environmental pollution. The microalgae consortia is able to utilize organic material as a source of nutrition for its growth, therefore may reduce pollutant. The aim of this research to determine effect rasio POME and microalgae consortia to growth rate microalgae. POME treatment using flat-photobioreactor with semicontinuous systems at variations POME : microalgae consortia 100:0; 80:20; 75:25; 70:30 (%, v/v). The results showed the best variation it POME : microalgae consortia in 70:30 (%, v/v), with growth rate 0,181/day, and TSS 38.000 mg/l. Keywords: Growth Rate, Microalgae Consortia, Palm Oil Mill Effluent (POME), Semicontinuous